2001
DOI: 10.1038/sj.leu.2401971
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary infiltrates at diagnosis have no prognostic significance in children with acute myeloid leukaemia

Abstract: This retrospective study was designed to review the relative frequency and prognostic significance of extramedullary infiltrates in children with acute myeloid leukaemia (AML). The registration data and initial discharge summaries were reviewed for all children diagnosed with AML, and registered by the Dutch Childhood Leukaemia Study Group (DCLSG). Between 1972 and 1998, 477 children were diagnosed with AML. Of these patients, 120 (25.1%) had extramedullary leukaemia (EML) at diagnosis. Four categories of EML … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
71
3
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 27 publications
9
71
3
2
Order By: Relevance
“…The finding that presenting WBC count was lower in the AML-M0 patients is interesting in view of previous reports suggesting that the M0 AML subtype is associated with an elevated presenting WBC count, a factor which may contribute to its generally unfavorable outcome. 28 Granulocytic sarcomas, reported to occur in up to 10% of children with AML, 29 have infrequently been documented in AML-M0 patients, 29,30 which is in keeping with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…The finding that presenting WBC count was lower in the AML-M0 patients is interesting in view of previous reports suggesting that the M0 AML subtype is associated with an elevated presenting WBC count, a factor which may contribute to its generally unfavorable outcome. 28 Granulocytic sarcomas, reported to occur in up to 10% of children with AML, 29 have infrequently been documented in AML-M0 patients, 29,30 which is in keeping with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Cytogenetic abnormalities included in the WHO classification of AML are crucial diagnostic and prognostic markers that serve to predict response to induction therapy, remission duration, and overall survival (Byrd et al, 2002). Although the prognostic significance of extramedullary involvement in AML is controversial Bisschop et al, 2001), MS cytogenetic abnormalities identified using array-CGH could aid in stratifying patients, based on genetics, especially in the absence of marrow cytogenetic abnormalities due to nonleukemic or nonanalyzable marrow samples.…”
Section: Discussionmentioning
confidence: 99%
“…22 The lack of cytogenetically cryptic disease in the present study in part reflects our ability to perform cytogenetic analyses on fresh (rather WBC, white blood cell; CNS, central nervous system status: 1, no blasts; 2, Ͻ5 WBC per l with blasts present; 3, Ͼ5 WBC per l with blasts present; GS, granulocytic sarcoma; FAB, French-American-British; EFS, event-free survival; Hem Rel, hematologic relapse; CR, complete remission; EM Rel, extramedullary relapse; haplo-HSCT, haploidentical hematopoietic stem cell transplantation; auto-HSCT, autologous hematopoietic stem cell transplantation; allo-HSCT, allogeneic hematopoietic stem cell transplantation. a Sites of GS include skull (patients 16,18,22,31,32), orbits (24,38), and spinal cord (6,14).…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] A recent study of 477 children with AML demonstrated that the presence of extramedullary leukemia, including GS, had no prognostic significance. 14 The t(8;21) disrupts the AML1:CBF␤ transcription factor complex and creates an AML1-ETO fusion gene, whose protein product includes the runt homology domain of AML1 fused to ETO. 15,16 Like the normal AML1 protein, AML1-ETO binds DNA and interacts with CBF␤.…”
Section: Introductionmentioning
confidence: 99%